Assessing the Use of Expanded Clay Aggregates With Limestone in Water Treatment - JohnBaptist Ian Busobozi (Uganda Christian University, 2025)
This study evaluated the effectiveness of limestone and expanded clay aggregates (ECA) in removing iron from water sourced from the Nyaruzinga water treatment plant Bushenyi. Batch experiments demonstrated that limestone effectively removed 95% of iron, reducing concentrations to 0.12 mg/L, which is below the WHO drinking water standard of 0.3 mg/L, with an optimal contact time of 5 minutes. A 10 cm deep ECA filtration bed, organized in layers of 4 mm, 3 mm, and 2 mm particles, provided a retention time of 24 seconds while removing the precipitates formed from limestone addition, further enhancing water quality. Manganese concentrations in the raw water were below 0.1 mg/L, which was attributed to complex formation with organic substances that adsorbed onto wetland sediments. Thus, while the combined treatment proved highly effective for iron removal, manganese removal could not be conclusively assessed. Additionally, the process improved water clarity and quality, with turbidity decreasing from 16 to 13.99 NTU, pH increasing from 7.2 to 7.4, and color reducing significantly from 638 to 83 PtCo. However, electrical conductivity increased from 48 to 125 µS/cm, and calcium levels rose from 3 to 12 mg/L, though all parameters remained within acceptable standards for potable water. Keywords: Iron removal, manganese, limestone, expanded clay aggregates, water treatment, wetlands, potable water quality
Undergraduate